2011
DOI: 10.1038/gt.2011.57
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor incorporated into herpes simplex virus vector accelerates facial nerve regeneration after crush injury

Abstract: Hepatocyte growth factor (HGF) promotes regeneration of the central nervous system, but its effects on the peripheral nervous system remain unclear. This study was conducted to elucidate the effect of HGF on regeneration of the murine facial nerve after crush injury. To do so, a replication-defective herpes simplex virus vector that incorporated HGF was prepared (HSV-HGF). The main trunk of the facial nerve was compressed by mosquito hemostats, and HSV-HGF, control vector or medium was then applied to the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…We also observed the phosphorylation of c‐Met in sciatic nerve explant cultures, which was suppressed by the c‐Met blockers (Figure d). In accordance with previous reports on the expression of HGF in normal nerves (Krasnoselsky et al, ; Esaki et al, ), we found that HGF was expressed in fibroblast‐like cells and vessels in the sciatic nerves using IF staining (Figure e), potentially indicating the paracrine action of secreted HGF on c‐Met receptor in SCs.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We also observed the phosphorylation of c‐Met in sciatic nerve explant cultures, which was suppressed by the c‐Met blockers (Figure d). In accordance with previous reports on the expression of HGF in normal nerves (Krasnoselsky et al, ; Esaki et al, ), we found that HGF was expressed in fibroblast‐like cells and vessels in the sciatic nerves using IF staining (Figure e), potentially indicating the paracrine action of secreted HGF on c‐Met receptor in SCs.…”
Section: Resultssupporting
confidence: 92%
“…The potential implication of the HGF/c‐Met signaling in nerve repair including peripheral nerves has been reported (Hashimoto et al, ; Kitamura et al, ). For example, HGF is normally present in sciatic nerves (Krasnoselsky et al, ) and virus‐mediated forceful HGF expression in the injured nerves enhanced peripheral nerve regeneration (Esaki et al, ). Even though the neurotrophic and axonotrophic effects of HGF provides a potential mechanism for the role of HGF in nerve repair (Davey et al, ; Ebens et al, ), we found significant activation of the HGF‐c‐Met‐Gab2 pathway in SCs after injury, and Gab2KO mice exhibited a defect in SC migration‐associated axonal regrowth.…”
Section: Discussionmentioning
confidence: 99%
“…The main neurotrophic factors used for peripheral nerve regeneration include nerve growth factor (NGF), glial cell line‐derived neurotrophic factor (GDNF), brain‐derived neurotrophic factor (BDNF), neurotrophin‐3, 4/5 (NT‐3, 4/5), ciliary neurotrophic factor (CNTF), and leukemia inhibitory factor (LIF) . Several studies have examined the effects of growth factors, such as pleiotrophin (PTN), hepatocyte growth factor (HGF), and vascular endothelial growth factor (VEGF), on peripheral nerve injury . However, applying one exogenous neurotrophin is often insufficient to stimulate the entire process of peripheral nerve regeneration, and the simultaneous up‐regulation of multiple neurotrophic factors remains challenging .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the half-life of these proteins is usually very short, [ 39 ] and the growth factors released into the environment may not be as bioactive. [ 90 ] The release kinetics varies depending on the system and factor used, and therefore the dose needs to be optimized.…”
Section: Other Neurotrophic Factorsmentioning
confidence: 99%